Apropriar-se: o acontecimento poético em contos de Clarice Lispector: (...à beira do abismo, estamos) - ATAÍDE, Luciana de Barros (Universidade Federal do Pará, 2019)
The present research intends to identify the relationship between Being, language and thought in narratives of Clarice Lispector, having as reference, mainly, stories that the writer produced throughout the life, from the "First stories" - narratives produced in the decade of 1940 - until the "Last Stories" - produced in the 1970s. In all, twenty one narratives will be studied in which the Being is in force as a matter. However, excerpts from other narratives will also be present, since the approach will be permeated by the search for the appropriative poetic event (Ereignis) through the problematization of the notions of writing and thinking, technique and art, being-alone and being-with, finitude and singularization, I and World. The intention is to show the intertwining ser-man-language-truth under the labyrinth of the question of origin. In Clarice's narratives emerges the investigative project that aims to unfold the essence of man that happens as language - since it is the home of Being and in his dwelling man lives - being a work of listening, understanding and interpretation of the Inherent Questions to the human condition. Thus, starting from the phenomenological-hermeneutic contribution, it will be possible to establish a relationship between Clarice Lispector's literature with thinkers such as Martin Heidegger (especially), Merleau-Ponty, Gaston Bachelard and Manuel Antônio de Castro, among others of great relevance for this study. Another reference of great importance that will support this study is the work The second sex (1980) of the thinker Simone de Beauvoir within the line of 'becoming' with regard to the human condition in possibilities and also with regard to the relation asymmetric gender that tends to reduce female freedom within society. Clarice not only worked as the word, but also with the thought that provides the perception of the velar and unveiling of the man, enabling him to the appropriation of himself, since it is a poetic saying that shows itself as the founding dimension of the condition human, revealed by overwhelming force for engendering a new worldview that lies beyond everyday superficiality. It is, therefore, in this study, narratives (tales) that expose Clarice's artistic-literary work in which poetry dwells in the proximity of thought by constructing a saying that evokes the essence of language.